Natural Course of Cytologically Benign Thyroid Nodules: Observation of Ultrasonographic Changes - Dong Jun Lim; Jee Young Kim; Ki Hyun Baek; Mee Kyoung Kim; Woo Chan Park; Jong Min Lee; Moo Il Kang; Bong Yun Cha (Endocrinology and Metabolism, 2013)
BackgroundThe natural course of cytologically benign thyroid nodules remains unclear. The aim of this study was to evaluate whether ultrasonographic (US) changes are associated with changes in nodule volume during follow-up.MethodsWe retrospectively reviewed over 4 years of clinical records of patients with benign thyroid nodules as confirmed by fine needle aspiration (FNA). In total, 186 patients with 202 benign thyroid nodules were included for study. We assessed for changes in nodule volume and examined the cystic portion of the nodule as well as four US features (echogenicity, margin, calcification pattern, and shape).ResultsDuring follow-up (mean, 21.7±10.7 months) and using 50% as a cutoff value, nodule volumes increased in 11.8%, exhibited no change in 79.9%, and decreased in 8.3% of patients. Proportion of nodules demonstrating at least one US change was 20.8% (42/202). The most common US changes (in descending order of frequency) were cystic change, margin change, and calcification pattern change. Nodule shape and echogenicity rarely changed. Increased nodule volume was not significantly associated with any US features or with the number of FNAs but was associated with younger age at time of diagnosis.ConclusionAlthough a portion of thyroid nodules confirmed as benign showed US changes or volume changes during the follow-up period, these findings may only represent the natural course of benign nodules. Frequent follow-up with US might be needed for only a small number of cases with suspicious US findings.